Students' Perception on Online Learning of Speaking for Discussion Course - Annisa Sakinah; Syafrizal Sabaruddin; Ildi Kurniawan (Journal of English Education and Teaching, 2023)
This research aims at finding out students' perceptions on online learning of speaking for discussion course at the English Education Study Program Universitas Bengkulu. This research was descriptive quantitative. The population of this research was the fourth-semester students of the English Education Study Program of Universitas bengkulu in the 2020/2021 academic year. The sample of this research was used total sampling method, totaling 115 students. The data were collected by using 25 items of the questionnaire which were divided into 3 parts, namely Perceptions of Usefulness (PU), Perceptions of Easy Use and Challenge Faced (PEUC), and Instructor/lecturer Characteristic (IC). This research used simple statistical to analized the data. The result of this study showed that students’ positive perception of online learning of speaking for discussion course was 63% which is much higher than negative perception which was only 37%. It means that online learning is good to use during the pandemic situation even though it still has aweaknesses that online learning does not really help them to improve their speaking skill.